Analytically optimal parameters of dynamic vibration absorber with negative stiffness. (15th February 2017) - Shen, Yongjun; Peng, Haibo; Li, Xianghong; Yang, Shaopu
Abstract: In this paper the optimal parameters of a dynamic vibration absorber (DVA) with negative stiffness is analytically studied. The analytical solution is obtained by Laplace transform method when the primary system is subjected to harmonic excitation. The research shows there are still two fixed points independent of the absorber damping in the amplitude-frequency curve of the primary system when the system contains negative stiffness. Then the optimum frequency ratio and optimum damping ratio are respectively obtained based on the fixed-point theory. A new strategy is proposed to obtain the optimum negative stiffness ratio and make the system remain stable at the same time. At last the control performance of the presented DVA is compared with those of three existing typical DVAs, which were presented by Den Hartog, Ren and Sims respectively. The comparison results in harmonic and random excitation show that the presented DVA in this paper could not only reduce the peak value of the amplitude-frequency curve of the primary system significantly, but also broaden the efficient frequency range of vibration mitigation. Highlights: A DVA with negative stiffness is presented. The optimal parameters of the DVA are analytically obtained. The design method for the negative stiffness is determined. The excellent performances of the DVA are illustrated.